Posttraumatic stress disorder among sexual harassment victims: the role of social support, resilience, and religious coping - Eko Sujadi; Muhd Odha Meditamar; Muhammad Fadhli; Jafar Ahmad; Yuserizal Bustami; Syaiful Indra (Intelektual Pustaka Media Utama, 2023)
Female students are still at risk of experiencing sexual harassment, which can lead to posttraumatic stress disorder (PTSD). This study investigated the impact of social support on PTSD female students who have been sexually harassed, as mediated by the resilience and religious coping. Out of a total of 1,439 female students who filed online self-reports, 170 female students reported being sexually harassed by lecturers, male students, and administrative officers. The PTSD checklist–civilian version (PCL-C), Multidimensional scale of perceived social support, brief resilience scale, and brief religious coping scale (RCOPE) were used to collect data. Partial least squares (PLS) modeling was used to test the developed hypothesis. This study found that social support, resilience, and religious coping all had an impact on PTSD. Furthermore, social support has an indirect effect on PTSD through resilience and religious coping. Because resilience and coping are mediators in recovering PTSD and that both can be intervened and modified, a training program specifically designed to improve both is needed to overcome the PTSD symptoms experienced by sexual harassment victims.